Temperature thresholds for germination in 20 short‐range endemic plant species from a Greenstone Belt in southern Western Australia. (21st January 2019) - Cochrane, A.
Abstract: The study of climate‐driven effects on seed traits such as germination has gained momentum over the past decade as the impact of global warming becomes more apparent on the health and survival of plant diversity. Seed response to warming was evaluated in a suite of short‐range endemic species from the biodiverse Greenstone Belt of southern Western Australia. The temperature dimensions for germination in 20 woody perennials were identified using small unreplicated samples over 6 weeks on a temperature gradient plate (constant and fluctuating temperatures between 5 and 40 °C). These data were subsequently modelled against current and forecast (2070) mean monthly minimum and maximum temperatures to illustrate seasonal changes to germination timing and final percentage germination. All but one species attained full germination in at least one cell on the gradient plate. Modelling of the data suggested only minimal changes to percentage germination despite a forecast rise in diurnal temperatures over the next 50 years. Nine species were predicted to experience declines of between <1% and 7%, whilst 11 species were predicted to increase their germination by <1% to 3%. Overall, the speed of germination is predicted to increase but the timing of germination for most species shifts seasonally (both advances and delays) as a result of changing diurnal temperatures. The capacity of this suite of species to cope with warmer temperatures during a critical early life stage shows a degree of adaptation to heterogeneous environments. Predicting the effects of global change on terrestrial plant communities is crucial to managing and conserving plant diversity.